Nudging Study Habits: A Field Experiment on Peer Tutoring in Higher Education - Nicholas Wilson; Todd Pugatch (Global Labor Organization (GLO), 2017)
More than two of every five students who enrolled in college in 2007 failed to graduate by 2013. Peer tutoring services offer one approach toward improving learning outcomes in higher education. We conducted a randomized controlled experiment designed to increase take-up of university tutoring services. Brief, one-time messages increased tutoring take-up by 7 percentage points, or 23% of the control group mean. Attendance at multiple tutoring sessions increased by nearly the same amount, suggesting substantial changes in study habits in response to a simple and inexpensive intervention. We find little evidence of advertising-induced tutoring on learning outcomes.
Keywords: D83; I23; 330; peer tutoring; human capital investment; behavioral response to advertising; nudges; higher education